Modelagem fotogramétrica e calibração de um sistema de visão omnidirecional - Marcato Junior, José [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Omnidirectional vision systems that enable 360° imaging have been widely used in several research areas including Close-Range Photogrammetry. The use of this system to acquire accurate measurement, which is the aim of Photogrammetry, requires two steps: sensor and platform mathematical modelling, relating features in the object space with the features in the image space; and the system calibration, in which the mathematical models parameters are estimated. The main aim is to develop the rigorous photogrammetric modelling and a calibration technique to an omnidirectional system composed of a camera and a conic mirror. The relationship between the object and image spaces is established using point features. The mathematical modelling is based on the camera projection model and on the properties of the conic mirror reflection. The system calibration technique is divided into inner and platform calibration. The inner calibration technique has the following steps: camera calibration; conic mirror modelling; and estimation of the parameters which relates the camera and cone reference systems. In the platform calibration, the parameters relating the imaging system and the direct georeferencing system, composed of a GNSS (Global Navigation Satellite System) receiver and an IMU (Initial Measurement Unity), were estimated...

Os sistemas de visão omnidirecional que permitem um campo de imageamento de 360° são usados em diversas áreas, incluindo a Fotogrametria à curta distância. O uso desses sistemas para obter medidas confiáveis, objetivo da Fotogrametria, exige duas etapas: modelagem matemática do sensor e da plataforma, que estabelece a relação entre feições no espaço objeto com as respectivas feições na imagem e; a calibração do sistema, em que os parâmetros dos modelos matemáticos são estimados. O objetivo principal consiste em desenvolver a modelagem fotogramétrica rigorosa e uma técnica de calibração para um sistema omnidirecional composto por uma câmara e um espelho cônico. A relação entre os espaços objeto e imagem é estabelecida por meio de entidades do tipo ponto. A modelagem matemática é baseada no modelo de projeção da câmara e nas propriedades de reflexão do espelho cônico. A calibração do sistema é dividida em calibração interna e da plataforma. A técnica de calibração interna do sistema apresenta as seguintes etapas: calibração da câmara; modelagem do espelho cônico e; estimação dos parâmetros de transformação entre os referenciais da câmara e do cone. Na calibração da plataforma foram estimados os parâmetros que relacionam o sistema de imageamento com o sistema de georreferenciamento direto, composto por receptor GNSS (Global Navigation Satellite System – Sistema global de navegação por satélite) e IMU (Inertial Measurement Unity – Unidade de Medida Inercial)...
Keywords: Cartografia; Fotogrametria; Calibração; Espelhos; Cameras eletronicas; Georreferenciamento; Cartography